A Data-Driven Framework for Digital Fire Pump Condition Monitoring and NFPA 25 Compliance Support in Industrial Buildings - Sholihuddin, Imam; Naba, Agus; Sucinintyas, Ika Karlina Laila Nur; Dharmawan, Hari Arief; Simatupang, Deo Dekri (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2026)
Fire pump systems are critical components of building fire protection infrastructure, yet their predominantly standby operation increases the risk of undetected failures between inspections. This study presents a digital monitoring framework for fire pump condition monitoring and NFPA 25 compliance support that continuously records hydraulic and operational data, automatically classifies weekly and annual test events, and generates structured digital records without modifying certified fire protection control functions. The framework was implemented in an industrial facility with electric- and diesel-driven fire pumps. Hydraulic evaluation of a Monoflo KP MX150-140 fire pump covered a flow range of 4,410–6,724 L/min (70.0%–106.7% of rated capacity). Digitalpressure measurements closely matched manual readings, with differences of 0.00–0.10 bar, and all 22 labeled test events werecorrectly identified. The system also enabled performance trending and reduced annual testing and documentation effortfrom approximately four days to 10–30 min (>90% reduction). Because the no-flow and 150% rated-flow conditions were notevaluated, the results represent a partial hydraulic assessment. Overall, the proposed human-in-the-loop framework improvesmonitoring visibility, inspection traceability, and audit readiness while supporting compliance-oriented digitalization.